Prevalence of mastocytosis and Hymenoptera venom allergy in the United States - Schuler, Charles F.; Volertas, Sofija; Khokhar, Dilawar; Yuce, Huseyin; Chen, Lu; Baser, Onur; Montejo, Jenny M.; Akin, Cem (Journal of allergy and clinical immunology, 2021)
Mastocytosis is a risk factor for Hymenoptera venom anaphylaxis (HVA). Current guidelines recommend measuring tryptase in patients with HVA and that those with mastocytosis pursue lifelong venom immunotherapy (VIT). Available data on HVA and mastocytosis largely derive from European single-center studies, and the prevalence of HVA with and without mastocytosis in the United States is unknown. We sought to determine the prevalence of HVA and mastocytosis in the United States using an insurance claims database and evaluate the impact of mastocytosis on VIT in patients with HVA in a US cohort. The IBM Watson Database, consisting of insurance claims from approximately 27 million US patients in 2018, was queried to identify patients with HVA and/or mastocytosis. Furthermore, a retrospective study of 161 patients undergoing VIT between 2015 and 2018 at the University of Michigan was conducted. In the IBM Watson Database, the prevalence of HVA was 167 per 100,000 (0.167%) and the prevalence of mastocytosis 10 per 100,000 (0.010%) overall and 97 per 100,000 (0.097%) among those with HVA. Mastocytosis showed a 9.7-fold increase among patients with HVA versus the general population. In the U-M cohort, 2.6% of patients with VIT had mastocytosis. Tryptase level did not correlate with venom reaction severity but was higher in patients with systemic VIT reactions. We observed a lower US HVA prevalence than previously reported. Mastocytosis was more common in US patients with HVA, though at lower rates than previously reported. In patients with VIT there was no correlation between tryptase level and reaction severity.